Diagnostic Performance of a Novel Multiplex PCR Assay for Candidemia among ICU Patients - Fuchs, Stefan (J Fungi (Basel), 2019)
Candidemia poses a major threat to ICU patients and is routinely diagnosed by blood culture, which is known for its low sensitivity and long turnaround times. We compared the performance of a novel, Candida-specific multiplex real-time PCR assay (Fungiplex(®) Candida IVD Real-Time PCR Kit) with blood culture and another established diagnostic real-time PCR assay (LightCycler SeptiFast Test) with respect to Candida detection from whole blood samples. Clinical samples from 58 patients were analyzed by standard blood culture (BC) and simultaneously tested with the Fungiplex Candida PCR (FP) and the SeptiFast test (SF) for molecular detection of Candida spp. Compared to BC, the FP test showed high diagnostic power, with a sensitivity of 100% and a specificity of 94.1%. Overall diagnostic accuracy reached 94.6%. Using SF, we found a sensitivity of 60%, a specificity of 96.1%, and an overall diagnostic accuracy of 92.9%. The Fungiplex Candida PCR has shown good sensitivity and specificity on clinical samples of high-risk patients for direct detection of Candida species in whole blood samples. Together with conventional diagnostics (BC and antigen testing), this new multiplex PCR assay may contribute to a rapid and accurate diagnosis of candidiasis.